2005
DOI: 10.1152/ajpgi.00004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia of rat stomach mobilizes ECL cell histamine

Abstract: Microdialysis was used to study how ischemia-evoked gastric mucosal injury affects rat stomach histamine, which resides in enterochromaffin-like (ECL) cells and mast cells. A microdialysis probe was inserted into the gastric submucosa, and the celiac artery was clamped (30 min), followed by removal of the clamp. Microdialysate histamine was determined by enzyme-linked immunosorbent assay. In addition, we studied the long-term effects of ischemia on the oxyntic mucosal histidine decarboxylase activity in omepra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Microdialysis monitoring of gastric ischemia during temporary celiac artery occlusion in anesthetised rats showed a more remarkable response to ischemia in the relative changes of metabolic ratios of lactate/pyruvate and lactate/glucose compared to changes in the flow indicator of H2O efflux and glycerol (105). Histamine release from enterochromaffin-like (ECL) cells during ischemia has been commonly sampled from the stomach submucosa with a single microdialysis probe (106)(107)(108)(109). However, submucosal microdialysis sampling has been suggested to be unrepresentative of histamine levels released from ECL cells, since these are located in the mucosa layer, requiring a diffusion of histamine from the mucosa to the submucosa and finally to the probe (110).…”
Section: Microdialysis Monitoringmentioning
confidence: 99%
“…Microdialysis monitoring of gastric ischemia during temporary celiac artery occlusion in anesthetised rats showed a more remarkable response to ischemia in the relative changes of metabolic ratios of lactate/pyruvate and lactate/glucose compared to changes in the flow indicator of H2O efflux and glycerol (105). Histamine release from enterochromaffin-like (ECL) cells during ischemia has been commonly sampled from the stomach submucosa with a single microdialysis probe (106)(107)(108)(109). However, submucosal microdialysis sampling has been suggested to be unrepresentative of histamine levels released from ECL cells, since these are located in the mucosa layer, requiring a diffusion of histamine from the mucosa to the submucosa and finally to the probe (110).…”
Section: Microdialysis Monitoringmentioning
confidence: 99%
“…Furthermore, microinfusion of the vasoconstrictor endothelin into the submucosa of the rat stomach causes local oxyntic mucosal injury (Whittle 1993;Norlén et al 2001;Bernsand et al 2003) and mobilizes large amounts of ECL-cell histamine (Norlén et al 2001;Bernsand et al 2003). Since both arterial clamping and endothelin microinfusion cause ischemia, we have suggested that hypoxia/anoxia contributes to the erosion of the mucosa and to the mobilization of histamine Kitano et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Clamping of the celiac artery for 30 min leads to extensive oxyntic mucosal damage (Kawai et al 1994) and causes mobilization of large amounts of histamine (Kitano et al 2005). Furthermore, microinfusion of the vasoconstrictor endothelin into the submucosa of the rat stomach causes local oxyntic mucosal injury (Whittle 1993;Norlén et al 2001;Bernsand et al 2003) and mobilizes large amounts of ECL-cell histamine (Norlén et al 2001;Bernsand et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microdialysis sampling in the stomach is presently performed with a probe implanted only into the submucosa. Most recently, stomach submucosal microdialysis sampling was used to study histamine release from enterochromaffin-like (ECL) cells [6][7][8][9]. ECL cells are; however, located in the mucosa layer while the microdialysis probes were implanted in the submucosa layer.…”
Section: Introductionmentioning
confidence: 99%